Optimization of the business management in the MSMEs of pothil in Mertoyudan, Regency Magelang - Farida Farida; Adam Bharesta Melano Samiaji; Natasyifa Ramadhanti; Deni Pebrianto; Della Aprilia Sari; Annisa Alfiyani Susanti (Universitas Muhammadiyah Magelang, 2024)
Gedongan Lor Village has significant potential for the development of pothil snack SMEs. However, most SMEs still face challenges in packaging, labeling, and business management. This activity aimed to provide understanding of labeling, packaging, simple bookkeeping, and NIB issuance. The objectives were achieved through socialization and training. The results showed that pothil snack SMEs were able to create new labels, conduct marketable packaging, and maintain simple bookkeeping. Additionally, all members of the pothil SME association have obtained a Business Identification Number (NIB) as a business legality.